Exploration epiphytic orchid and phorophyte in University of Phayao - Srimuang, Kanokorn; Chanvichit, Pavinee; Seramethakul, Trin (Health Science, Science and Technology Reviews, 2019)
The epiphytic orchid diversity and host specificity were examined at the natural forest of University of Phayao. Twenty-three species from twelve genus of orchids occur in the area. The genus Dendrobium showed the highest number of species and most abundant e.g. Cleisostoma fuerstenbergianum F. Kranzl., Dendrobium lindleyi Steud. and D. draconis Rchb.f.. Thirteen species of tree were orchid host (phorophyte). Orchid species in the area tend to occur on rough bark hosts but not specificity. Dipterocarpus tuberculatus Roxb. and Shorea obtusa Wall. were most important phorophytes in our study site. The zone preference and the distribution of orchid on phorophyte zone occur only zone two, three and four.